Theoretical prediction of maximum Curie temperatures of Fe-based dilute magnetic semiconductors by first-principles calculations. (3rd June 2019) - Fukushima, Tetsuya; Shinya, Hikari; Masago, Akira; Sato, Kazunori; Katayama-Yoshida, Hiroshi
Abstract: We clarify the maximum Curie temperatures in Mn- and Fe-based dilute magnetic semiconductors by first-principles calculations. For this purpose, the electronic structure and magnetic properties in the spinodal-decomposed zinc-blende type MnAs, MnSb, FeAs, and FeSb are calculated by the Korringa-Kohn-Rostoker Green's function method combined with the variational pseudo self-interaction correction. Our calculations clearly show that these zinc-blende materials have a possibility of very high Curie temperature by an n - or p -type Fermi level shift, and that the estimated Curie temperature by the mean field approximation reaches 1 000 K.